2011
DOI: 10.1097/id.0b013e31820031ab
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life After Implant-Retained Prosthetically Reconstructed Maxillae and Mandibles Postcancer Treatments

Abstract: Reconstruction and rehabilitation of the jaws affected by tumor restores the patient anatomically, esthetically, and functionally to optimum levels. However, a study with larger numbers of patients is necessary to ascertain the benefits of this treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Dental implants belong to rehabilitation if patient is disease free, motivated and in good condition and the bony structure allows implant surgery. Irradiation has a negative impact on bone regeneration and it is shown that failure rate on dental implantation raises due to irradiation of the fibular bone flap [14,15]. This might argue on behalf of the preoperative irradiation or chemoradiation if combination therapy is needed as it is saving the microvascular bone flap from irradiation in the treatment protocol.…”
Section: Discussionmentioning
confidence: 96%
“…Dental implants belong to rehabilitation if patient is disease free, motivated and in good condition and the bony structure allows implant surgery. Irradiation has a negative impact on bone regeneration and it is shown that failure rate on dental implantation raises due to irradiation of the fibular bone flap [14,15]. This might argue on behalf of the preoperative irradiation or chemoradiation if combination therapy is needed as it is saving the microvascular bone flap from irradiation in the treatment protocol.…”
Section: Discussionmentioning
confidence: 96%
“…Significant improvement in prosthesis and patients' satisfaction with implant‐retained prosthesis compared to non‐implant‐retained prosthesis was observed . General QoL and oral function, including chewing ability, speech, and swallowing subjective evaluation after implant‐prosthetic treatment, showed no significant improvement compared to the preoperative condition . However, the European Organization for Research and Treatment of Cancer head and neck module questionnaire and the Oral Health Impact Profile questionnaire showed beneficial changes in some items after implant‐prosthetic treatment .…”
Section: Resultsmentioning
confidence: 90%
“…The report period in most of the publications was between 4 and 36 months, and one publication reported up to 18 years (Table ). Among these publications, six reported mandibular cases, one reported maxillary cases, and one reported both mandibular and maxillary cases . Split skin graft, soft tissue free flap, fibula‐vascularized free flap, or primary closure were performed after ablative surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations